2011
DOI: 10.1016/j.archoralbio.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

MMP1 and MMP20 contribute to tooth agenesis in humans

Abstract: Our findings provide evidence that MMP1 and MMP20 play a role in human tooth agenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
1
16
0
2
Order By: Relevance
“…Environmental and epigenetic factors as well as genes regulating odontogenesis require further in vivo and in vitro investigation in order to better explain the phenotypic heterogeneity and to increase our knowledge about the odontogenic process (Swinnen et al, 2008). In spite of recent developments, data regarding the genes responsible for the less severe forms of hypodontia are still scarce and controversial (Kuchler et al, 2010). A study of familiar aggregation in a Portuguese population of sixty-two probands with MLIA and 142 first-degree relatives showed that the relative risk (RR) for a first-degree relative of an i n d i v i d u a l w i t h M L I A t o h a v e t h e s a m e t y p e o f a g e n e s i s w a s 1 5 t i m e s h i g h e r w h e n compared with a relative of an individual without that agenesis.…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental and epigenetic factors as well as genes regulating odontogenesis require further in vivo and in vitro investigation in order to better explain the phenotypic heterogeneity and to increase our knowledge about the odontogenic process (Swinnen et al, 2008). In spite of recent developments, data regarding the genes responsible for the less severe forms of hypodontia are still scarce and controversial (Kuchler et al, 2010). A study of familiar aggregation in a Portuguese population of sixty-two probands with MLIA and 142 first-degree relatives showed that the relative risk (RR) for a first-degree relative of an i n d i v i d u a l w i t h M L I A t o h a v e t h e s a m e t y p e o f a g e n e s i s w a s 1 5 t i m e s h i g h e r w h e n compared with a relative of an individual without that agenesis.…”
Section: Etiologymentioning
confidence: 99%
“…In spite of recent progress, the etiopathogenesis of hypodontia remains largely unknown (Kuchler et al, 2010;Vastardis, 2000;Kapadia et al, 2007). There is evidence that congenital tooth absence can be the result of environmental or hereditary causes, or even of their interaction (Schalk-van der Weide & Bosman, 1996;Swinnen et al, 2008).…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genetic studies have provided information about a number of genes related to tooth agenesis. Several genetic variations and mutations in AXIN2 (7), BMP4 (8), MMPs (MMP1 and MMP20) (9), PAX9 (10,11), MSX1 (10), TGFB3 (8), and WNT10A (12,13) have been associated with tooth developmental failure.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, Kuchler y colaboradores 32 estudiaron la asociación de MMP-1, MMP-3 y MMP-20, y su relación con agenesias dentales en 167 familias nucleares de dos poblaciones diferentes, 116 de Brasil y 51 de Turquía. Los participantes tenían al menos un diente ausente.…”
Section: Studies In Humansunclassified